ROLE OF INFORMATION TECHNOLOGY IN INDIAN INSURANCE INDUSTRY (International Journal of Food and Nutritional Sciences, 2022)
Individuals, businesses and other organizations face various risks in their various activities and insurance helps to protect them against these risks. Insurance plays an important role in our individuals, trade, industry, etc. Today, information technology affects every field, including the insurance sector. Insurance companies use information technology to provide better customer service, reduce costs, design and develop new products, etc. in order to Against this backdrop, this paper studies the role of information technology in the Indian insurance sector and its impact on insurance sector. The study found that elements such as time saving, ease of use, convenience, accessibility, accuracy of the premium amount, independent of insurance agents, significantly influence customers to access and use online insurance services.